GA-MIMO: Genetic Algorithm for Optimization of ESPAR Antenna on Beamspace MIMO - Rissa Rahmania; Bambang Setia Nugroho; Fiky Yosef Suratman; Suryo Adhi Wibowo (Website, 2019)
An electronically steerable passive array radiator (ESPAR) antenna can be used on a beamspace (BS)-multiple input multiple output (MIMO) system to reduce the device complexity. An ESPAR antenna has beamforming ability with single RF chain. However, antenna structure and channel conditions affect the number of orthogonal basis pattern which generated using Gram-Schmidt method. Based on this problem, reactance value at each parasitic element need to be optimized to form radiation pattern that required by the BS-MIMO. In this research, Genetic Algorithm (GA) is used to optimize reactance value which represented by the correlation between the desired and achieved radiation pattern, in different number of elements and different channel condition. GA is selected because this problem can be modeled as chromosome and several individual. Furthermore, the result shows in channel-ignorant and channel-aware, antenna with seven elements has a correlation in median value of 99.46% and 90.58%, respectively. Antena electronically steerable passive array radiator (ESPAR) dapat digunakan dalam sistem beamspace (BS)-multiple input multiple output (MIMO) dalam mengatasi kompleksitas perangkat. Antena ESPAR memiliki kemampuan untuk membentuk pola radiasi pada arah tertentu dengan menggunakan terminal tunggal, namun struktur antena dan kondisi kanal mempengaruhi pola dasar ortogonal yang dihasilkan melalui metode Gram Schmidt. Berdasarkan permasalahan tersebut, nilai reaktansi pada setiap elemen parasit perlu dioptimasi sehingga dapat menghasilkan pola radiasi yang dibutuhkan oleh sistem BS-MIMO. Pada penelitian ini, Algoritma Genetika digunakan untuk mengoptimasi nilai reaktansi yang direpresentasikan melalui korelasi antara pola radiasi yang dibutuhkan dengan pola radiasi yang dihasilkan, dalam jumlah elemen yang berbeda dan kondisi kanal yang berbeda. AG dipilih karena permasalahan ini dapat dimodelkan sebagai kromosom dan beberapa individual. Hasil analisis pada kondisi channel-ignorant dan channel-aware menunjukkan bahwa antena dengan tujuh elemen memiliki korelasi nilai median sebesar 99,46% dan 90,58%.